2010
DOI: 10.1523/jneurosci.0106-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Is Required for Persistent Epileptiform Activity in the Disinhibited Neocortical Brain Slice

Abstract: The neurotransmitter glutamate is recycled through an astrocytic-neuronal glutamate-glutamine cycle in which synaptic glutamate is taken up by astrocytes, metabolized to glutamine, and transferred to neurons for conversion back to glutamate and subsequent release. The extent to which neuronal glutamate release is dependent upon this pathway remains unclear. Here we provide electrophysiological and biochemical evidence that in acutely disinhibited rat neocortical slices, robust release of glutamate during susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 69 publications
3
49
2
3
Order By: Relevance
“…2). Owing to the importance of the glutamateglutamine cycle for replenishment of neurotransmitter pools (69,(93)(94)(95), inhibition of glycogen degradation may lead to decrements in neuronal glutamate synthesis. In agreement with this, it was demonstrated that glutamate-glutamine cycle activity (Fig.…”
Section: Role Of Glycogen Phosphorylase Isoforms For Glycogen Shunt Amentioning
confidence: 99%
“…2). Owing to the importance of the glutamateglutamine cycle for replenishment of neurotransmitter pools (69,(93)(94)(95), inhibition of glycogen degradation may lead to decrements in neuronal glutamate synthesis. In agreement with this, it was demonstrated that glutamate-glutamine cycle activity (Fig.…”
Section: Role Of Glycogen Phosphorylase Isoforms For Glycogen Shunt Amentioning
confidence: 99%
“…The prevailing view, however, has been that glutamine released from astrocytes is the predominant source of glutamate in glutamatergic terminals (Van den Berg and M A N U S C R I P T Garfinkel, 1971;Benjamin and Quastel, 1972;Hertz et al, 1999;Sibson et al, 2001) especially in situations of high demand such as persistent epileptiform activity (Tani et al, 2010;Tani et al, 2014). The idea has been that glutamate is taken up by astrocytes, converted to glutamine by the action of the astroglial enzyme glutamine synthetase (GS) in an ATP-dependent manner, released, taken up by axon-terminals and converted back to glutamate by means of phosphate activated glutaminase (Erecinska and Silver, 1990;Marcaggi and Coles, 2001;Hertz, 2013).…”
Section: Eaat2 In Terminals Will Short-circuit the Glutamate-glutaminmentioning
confidence: 99%
“…Indeed, glial cells are enriched with G-protein-coupled receptors, and their activation by glutamate, GABA, or other neurotransmitters are important endogenous triggers of PKC activation (Beckman et al, 1999). Complementary expression of both system A and non-system A transporters has been demonstrated on neurons, and it has been shown that the availability of glutamine regulates generation of the fast neurotransmitters (Rae et al, 2003;Jenstad et al, 2009;Solbu et al, 2010;Tani et al, 2010) and shapes the quantal size Liang et al, 2006;Fricke et al, 2007). Thus, SN1 may represent a key target for regulation of the glutamate/GABA-glutamine cycle (Fig.…”
Section: Functional Implications Of Sn1 Phosphorylationmentioning
confidence: 99%